Fabrication and Characterization of Glass‐Ceramic Fiber‐Containing Cr3 + ‐Doped ZnAl2O4 Nanocrystals. Issue 9 (30th June 2015) - Fang, Zaijin; Zheng, Shupei; Peng, Wencai; Zhang, Hang; Ma, Zhijun; Zhou, Shifeng; Chen, Danping; Qiu, Jianrong; Pinckney, L.
<x xml:space="preserve">Abstract</x> Glass‐ceramic fibers containing Cr3+‐doped ZnAl2O4 nanocrystals were fabricated by the melt‐in‐tube method and successive heat treatment. The obtained fibers were characterized by electro‐probe micro‐analyzer, X‐ray diffraction, Raman spectrum and high‐resolution transmission electron microscopy. In our process, fibers were precursor at the drawing temperature where the fiber core glass was melted while the clad was softened. No obvious element interdiffusion between the core and the clad section or crystallization was observed in precursor fiber. After heat treatment, ZnAl2O4 nanocrystals with diameters ranging from 1.0 to 6.3 nm were precipitated in the fiber core. In comparison to precursor fiber, the glass‐ceramic fiber exhibits broadband emission from Cr3+ when excited at 532 nm, making Cr3+‐doped glass‐ceramic fiber a promising material for broadband tunable fiber laser. Furthermore, the melt‐in‐tube method demonstrated here may open a new gate toward the fabrication of novel glass‐ceramic fibers.